Empowering Financial Futures: The Impact of Sharia Financial Literacy, Spiritual Intelligence, and Pocket Money Management - Saragih, Intan Lestari; Marlya Fatira; Ismi Affandi; Rahmadani, Rahmadani; Nurlinda, Nurlinda (CV. ULIL ALBAB CORP, 2026)
This study aims to determine the effect of Islamic financial literacy, spiritual intelligence, and pocket money usage on the financial management of students majoring in Islamic Finance and Banking in Medan. The sample used in this study consisted of 140 respondents who were students majoring in Islamic Finance and Banking at the Medan State Polytechnic, the State Islamic University of North Sumatra, and the Muhammadiyah University of North Sumatra in Medan City, who were given questionnaires. This study used a quantitative method with multiple linear regression analysis. This study conducted a Pearson correlation test, partial test (t), simultaneous test (f), and determination test (R2) with a significance level of 5% (α=0.05), processed with the help of SPSS version 26. The results of this study indicate that the variable of Islamic financial literacy has a significant effect on financial management, the variable of spiritual intelligence does not have a significant effect on financial management, and the variable of pocket money usage has a significant effect on financial management. The variables of Islamic financial literacy, spiritual intelligence, and pocket money usage significantly affect the financial management of students in the Islamic Finance and Banking Study Program in Medan City.